2003
DOI: 10.1152/ajpheart.00759.2002
|View full text |Cite
|
Sign up to set email alerts
|

Reduced perivascular Po2 increases nitric oxide release from endothelial cells

Abstract: Many studies have suggested that endothelial cells can act as "oxygen sensors" to large reductions in oxygen availability by increasing nitric oxide (NO) production. This study determined whether small reductions in oxygen availability enhanced NO production from in vivo intestinal arterioles, venules, and parenchymal cells. In vivo measurements of perivascular NO concentration ([NO]) were made with NO-sensitive microelectrodes during normoxic and reduced oxygen availability. During normoxia, intestinal first-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
49
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 40 publications
10
49
0
Order By: Relevance
“…This relationship is consistent with some experimental reports [42]; however, reports of other experiments [43] have indicated that small reductions in perivascular PO 2 increase NO release. This apparent discrepancy could be explained by the phenomenon of the peak values of NOS1 catalysis.…”
Section: Discussionsupporting
confidence: 93%
“…This relationship is consistent with some experimental reports [42]; however, reports of other experiments [43] have indicated that small reductions in perivascular PO 2 increase NO release. This apparent discrepancy could be explained by the phenomenon of the peak values of NOS1 catalysis.…”
Section: Discussionsupporting
confidence: 93%
“…The model predictions of ϳ30% lower NO concentration in the venular endothelium compared with the arteriolar endothelium are also similar to the reported ϳ 25% lower NO concentration in paired venules and arterioles by Nase et al (32). Although the magnitude of the difference is similar, the NO concentration predicted in the present model is significantly different from the measured one.…”
Section: Implications For In Situ Measurements Of Nosupporting
confidence: 88%
“…Although the magnitude of the difference is similar, the NO concentration predicted in the present model is significantly different from the measured one. The predicted NO concentrations are in the range of 104 and 69 nM for the arteriolar and the venular endothelium, respectively ( Table 2, case 1), compared with a measured NO concentration of 397 and 298 nM, respectively (32). This high NO concentration can be obtained from the present model by 1) increasing endothelial NO release (see Fig.…”
Section: Implications For In Situ Measurements Of Nosupporting
confidence: 50%
“…Carbon fiber, recessed-tip glass microelectrodes were used with a polarographic technique to measure [NO] in the intestine. NO-sensitive microelectrodes have been used in past studies in our laboratory (8,10,27). The production and calibration of the NO-sensitive microelectrodes were based on our lab's experience and techniques developed by Buerk and colleagues (13) and Freidemann et al (16).…”
Section: Methodsmentioning
confidence: 99%